Efficient Nucleophilic Degradation of an Organophosphorus Pesticide “Diazinon” Mediated by Green Solvents and Microwave Heating - Millán, Daniela; Tapia, Ricardo A.; Pavez, Paulina (Frontiers in Chemistry, 2019)
An efficient strategy for the degradation of organophosphate pesticide Diazinon was investigated. In this work, ionic liquids, bio-based solvents, and two conventional organic solvents were used as reaction media. Kinetics studies by means of half-lives (t1/2,h) were followed by 31P NMR and the products analyzed by GC-MS, HPLC-MS and NMR techniques. These results have shown that t1/2 values in ionic liquids were the lowest and also they were able to activate two electrophilic centers in Diazinon, whilst degradation in bio-based solvents occurred slowly by only an aromatic pathway. In addition, a study to estimate the influence of green activation techniques was carried out by using Ultrasound irradiation and Microwave heating in combination with greener solvents and two conventional organic solvents. Under Microwave heating, faster degradation than under ultrasound irradiation was found. Finally, considering both families of solvent used here and their behavior under green activation techniques, we propose that the more efficient way for degradation of Diazinon with piperidine is by microwave heating using ionic liquids as solvents..